CD4 T cell regeneration in HIV-1 elite controllers - YANG, Yue (2012)
BACKGROUND: Elite controllers spontaneously control HIV-1 replication, which in many cases is associated with preservation of normal CD4 T cell counts. However, a subset of elite controllers has progressive CD4 T cell losses despite undetectable viral loads, for reasons that remain undefined. Here, we assessed mechanisms of CD4 T cell homeostasis in elite controllers with progressive vs. non-progressive HIV-1 disease courses. METHODS: Flow cytometry assays were used to determine the proliferation, activation and apoptosis levels of naïve T cells in elite controllers with high or low CD4 T cell counts, and reference cohorts of HIV-1 negative and HAART-treated persons. Thymic output was measured by sjTREC/βTREC ratios, and the frequency of circulating recent thymic emigrants was flow-cytometrically determined by surface expression of protein tyrosine kinase 7 (PTK7). RESULTS: Proportions of naïve T cells in elite controllers were severely reduced and closely resemble those of HIV-1 patients with progressive disease. Despite reductions of naïve T cells, most elite controllers were able to maintain normal total CD4 T-cell counts by preservation of uncompromised thymic function in conjunction with extrathymic processes that led to elevated levels of circulating recent thymic emigrants. In contrast, elite controllers with low CD4 T-cell counts had reduced thymic output that mirrored thymic dysfunction during untreated progressive HIV-1 infection. CONCLUSION: These results indicate that both thymic and extrathymic mechanisms contribute to CD4 T cell maintenance in elite controllers and support the idea that CD4 T-cell homeostasis and control of viral replication are distinct, but frequently coinciding processes